Leveraging Technology for MSME Development: A Case Study of the Sistem Informasi Hasil Desa (SIHASA) V2 in Banyumas Regency - Prabowo, Wahyu Adi; Putri, Tiara Pebriana; Himawan , Zidan Yazid (Politeknik Ganesha Medan, 2023)
Banyumas Regency in Central Java Province comprises 27 districts and 331 villages, showcasing its vast geographical coverage. Over three years, from 2006 to 2009, the region witnessed a notable increase in small businesses, rising from 643 to 717 establishments. Despite this growth, MSMEs in Banyumas face a prevalent challenge of inadequate information dissemination for effectively promoting their products. To tackle this issue, a proposed solution is the Village Results Information System (SIHASA) V2 website. This website supports village communities, MSMEs, and governments in managing their respective activities and operations. To expedite the creation of the system, the Rapid Application Development (RAD) method is employed, encompassing essential stages such as project requirement determination, prototype creation, development processes, and gathering feedback. Furthermore, to ensure an efficient system design, the implementation of Unified Modeling Language (UML) is integrated, incorporating crucial components like Use Case Diagrams and Class Diagrams. This meticulous design approach guarantees that the system effectively caters to the community's diverse needs, specifically benefiting the village community in Banyumas Regency in terms of managing village products and facilitating efficient MSME operations. The outcomes of this research endeavor hold significant promise for the community, providing practical tools and resources to enhance their livelihoods and contribute to the overall development of the Banyumas Regency.